Peningkatan Infrastruktur Jaringan Internet Melalui Antena LiteBeam 5 GHz - Wahyu Indra Tama (Journal of Informatics Management and Information Technology, 2024)
SMK Negeri 1 Kutalimbaru, as an educational institution, understands that a fast and reliable internet connection is the key to supporting an effective teaching and learning process. However, the current situation still has obstacles related to the quality of the local internet network at SMK Negeri 1 Kutalimbaru, this causes the teaching and learning process and the implementation of computer-based exams in the computer laboratory to be constrained and not optimal. The purpose of this study is to optimize the quality of the computer laboratory internet network at SMK Negeri 1 Kutalimbaru by implementing LiteBeam 5 GHz antenna technology using point-to-point protocol and collecting data on the quality of the school computer laboratory internet network before and after implementing LiteBeam 5 GHz antenna technology on the SMK Negeri 1 Kutalimbaru internet network infrastructure. This study uses the QoS (Quality of Service) method with parameters of throughput, packet loss, latency and jitter. The results of the study of measuring the quality of the school computer laboratory internet network before the implementation of LiteBeam 5 GHz antenna technology on the SMK Negeri 1 Kutalimbaru internet network infrastructure when used by 5 users obtained an overall QoS index value of 3.25 which is in the "good" category. While when used by 30 users, the overall QoS index value was 3 which is in the "good" category. Measurement of the quality of the school computer laboratory internet network after the implementation of LiteBeam 5 GHz antenna technology on the SMK Negeri 1 Kutalimbaru internet network infrastructure when used by 5 users, the overall QoS index value was 4 which is in the "very good" category. While when used by 30 users, the overall QoS index value was 4 which is in the "very good" category. Based on the results of the measurement of the school computer laboratory internet network, it is concluded that the implementation of LiteBeam 5 GHz antenna technology on the SMK Negeri 1 Kutalimbaru internet network infrastructure has succeeded in providing an optimal improvement in the quality of the school computer laboratory internet network